High heat transfer aluminum alloy material, embryo tube, high heat transfer and high corrosion resistance aluminum tube and their production process
By adjusting the material composition of the aluminum alloy and adopting hot-dip galvanizing process, the problem of insufficient thermal conductivity and corrosion resistance of 3-series aluminum alloy is solved, and high heat transfer and high corrosion resistance of aluminum tube materials are achieved, reducing production costs.
Patent Information
- Application Number
- CN202510028202.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
AI Technical Summary
The existing 3-series aluminum alloys have insufficient thermal conductivity in the field of heat exchange and are weak in corrosion resistance, making it difficult to replace copper tubes. Increasing the internal thread angle and tooth height will increase spinning difficulty and production costs.
By adjusting the material composition of the aluminum alloy, the Mn element content is reduced, the Al element content is increased, and a very small amount of Sr element is added to promote the precipitation of the AlMn phase and improve the heat transfer performance of the aluminum alloy. At the same time, a stable zinc-aluminum composite coating is formed by using hot-dip galvanizing process to enhance corrosion resistance.
It significantly improves the heat transfer and corrosion resistance of aluminum alloys, reduces production costs, and the stability and uniformity of zinc-aluminum composite coating improves the long-term corrosion resistance of aluminum pipes.
Abstract
Description
Technical Field
[0001] The present invention relates to a high heat transfer aluminum alloy material, an embryonic tube, a high heat transfer and high corrosion resistance aluminum tube and their production processes, belonging to the technical field of aluminum alloy materials. Background Art
[0002] In the field of heat exchange equipment such as air conditioning and refrigeration, the performance of the heat exchanger directly determines the energy efficiency level and service life of the equipment, and the heat exchange pipe is the core component of the heat exchanger and plays a decisive role in the heat exchange efficiency. According to the shape of the pipe, the heat exchange pipe can be divided into round pipe, straight tooth pipe and internal thread pipe, among which the internal thread pipe has better performance.
[0003] Traditional internally threaded copper tubes have long dominated the heat exchange field. Through the unique grooves and toothed structures on the inner surface, they effectively increase the heat exchange surface area and promote turbulence in the fluid, thereby significantly improving the heat exchange efficiency. However, with the increasing market competition, finding a material with efficient heat transfer capabilities to replace the expensive copper has become a top priority for the development of the industry.
[0004] In recent years, aluminum and aluminum alloys have gradually emerged in the field of heat exchange due to their better thermal conductivity, corrosion resistance, light weight and low cost compared to other metals except copper and silver. In particular, 3 series aluminum alloys are gradually becoming an alternative to copper for the manufacture of radiator tubes.
[0005] Although 3 series aluminum alloys have good corrosion resistance and excellent cold working performance in the aluminum alloy family, their thermal conductivity is only at a medium level, which is far behind that of copper tubes. At present, the common method is to increase the internal thread angle and tooth height to achieve a level of heat dissipation equivalent to that of copper tubes. However, the problem caused by increasing the internal thread angle and tooth height is that the difficulty of spinning the internal thread teeth increases, and the production efficiency decreases.
[0006] Moreover, the corrosion resistance of 3 series aluminum alloy is weaker than that of copper tube, so a zinc layer needs to be set for corrosion protection. In the prior art, aluminum alloy pipes are provided with a zinc layer by a zinc spraying process, and the zinc layer protects the aluminum substrate by means of a sacrificial anode. The zinc layer on the surface of the aluminum substrate has a high concentration and a fast uniform corrosion rate. When this part of the zinc layer is sacrificed and corroded to the inner layer of the aluminum substrate, the corrosion rate gradually slows down due to the gradual decrease in the concentration of the zinc layer infiltrated into the aluminum substrate, and the corrosion resistance effect really begins to play a role. However, the corrosion resistance layer formed by this part of the inner zinc layer is usually only tens of microns, which cannot meet the requirements of long-term corrosion resistance under actual working conditions. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a high heat transfer aluminum alloy material, a embryo tube, a high heat transfer and high corrosion resistance aluminum tube and their production processes. The heat transfer performance of the aluminum alloy is improved by adjusting the material composition, and on this basis, an aluminum tube with excellent corrosion resistance is manufactured.
[0008] The first aspect of the present invention relates to a high heat transfer aluminum alloy material, comprising the following components:
[0009] Mn: 0.35~0.55wt%, Si: 0.05~0.13wt%, Fe: 0.05~0.13wt%, Mg: 0.06~0.15wt%, Cr: 0.03~0.10wt%, Cu: 0.05~0.15wt%, Zn: 0.07~0.15wt%, Ti: 0.05~0.20wt%, Sr: 0.008~0.012wt%, and the balance is Al and unavoidable impurities.
[0010] For example, the content of Mn element can be 0.35wt%, 0.40wt%, 0.45wt%, 0.50wt%, 0.55wt%, etc.;
[0011] For example, the content of Si element can be 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, etc.;
[0012] For example, the content of Fe element can be 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, etc.;
[0013] For example, the content of Mg element may be 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, etc.;
[0014] For example, the content of Cr element may be 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, etc.;
[0015] For example, the content of Cu element can be 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, etc.;
[0016] For example, the content of Zn element can be 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, etc.;
[0017] For example, the content of Ti element can be 0.05wt%, 0.07wt%, 0.09wt%, 0.10wt%, 0.12wt%, 0.13wt%, 0.15wt%, 0.18wt%, 0.20wt%, etc.;
[0018] For example, the content of the Sr element may be 0.008 wt%, 0.009 wt%, 0.010 wt%, 0.011 wt%, 0.012 wt%, etc.
[0019] Compared with the proportion of 1.00-1.50wt% in conventional 3 series aluminum alloys, the Mn element content in the present invention is greatly reduced, the Mn element content is reduced, the Al element content is increased, the solid solubility of Mn in the aluminum matrix is reduced, and the heat transfer performance of the aluminum alloy is improved; on this basis, the present invention promotes the precipitation of AlMn phase during annealing by adding a very small amount of Sr element, further reduces the solid solubility of Mn in the aluminum matrix, and improves the heat transfer performance of the aluminum alloy.
[0020] While the reduction in the content of Mn elements improves the heat transfer performance of aluminum alloys, it also causes a decrease in its strength, which is not conducive to cold processing. The added Sr element also plays a role in refining the grains of the aluminum alloy. The refined grains can make the aluminum alloy deform more evenly during the cold forming process, reduce the risk of cracking or defects caused by excessive local deformation, and improve the cold processing performance of the aluminum alloy to a certain extent; but the added Sr element content is very small, which is not enough to make up for this defect; therefore, the present invention also adds appropriate amounts of Mg, Si, Cu, Zn, and Ti elements to make up for the insufficient cold processing performance of the aluminum alloy caused by the reduction in the content of Mn elements. The addition of Mg, Si, Cu, Zn, Sr, and Ti elements should not exceed the above range, otherwise large-particle precipitation phases are likely to appear, which will affect the corrosion resistance of the matrix.
[0021] A second aspect of the present invention relates to a production process of the above-mentioned high heat transfer aluminum alloy material, comprising the following steps:
[0022] Smelting step: weighing raw materials according to the weight percentage of elements in the aluminum alloy material for smelting to obtain a melt; preferably, the raw materials include aluminum ingots, aluminum-manganese alloys, silicon blocks, aluminum-iron alloys, pure magnesium ingots, aluminum-chromium alloys, pure copper particles, pure zinc ingots, aluminum-titanium alloys and strontium;
[0023] Refining step: Use inert gas refining or refining agent refining to remove inclusions and hydrogen in the melt to ensure that the hydrogen content in the melt is less than 0.15ml / 100g;
[0024] Casting step: when the melt temperature is in the range of 700-750° C., casting is performed at a speed of 40-80 mm / min to obtain a cast rod, and a grain refiner is added to the flow channel before casting; preferably, a gas sliding mold semi-continuous casting method is used for casting;
[0025] Homogenizing step: Place the cast rod in a homogenizing furnace and heat it up with the furnace at a heating rate of not less than 400°C / h to between 550 and 610°C for insulation for 5 to 12 hours, then take it out of the furnace for natural cooling.
[0026] The casting speed in the casting step can be 40 mm / min, 50 mm / min, 60 mm / min, 70 mm / min, 80 mm / min, etc.
[0027] The heating rate in the homogenization step can be 400°C / h, 450°C / h, 500°C / h, 550°C / h, 600°C / h, etc., and the insulation temperature can be 550°C, 570°C, 600°C, 610°C, etc.
[0028] The insulation time in the homogenization step can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.
[0029] For some specific embodiments, the grain refiner is AlTi5B1 and / or AlTi5B0.2, the grain refiner addition temperature is 710-725°C, and the addition amount is 0.5%-1.0% of the melt weight. For example, the addition amount can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. of the melt weight.
[0030]
[0013] A third aspect of the present invention relates to a high heat transfer aluminum alloy embryo tube, which is a straight tooth aluminum tube or a common round aluminum tube with smooth inner and outer surfaces, and is made by first heating and then extruding the high heat transfer aluminum alloy material. Preferably, the embryo tube has an outer diameter of 4-40 mm and a wall thickness of 0.4-5 mm.
[0031] For some specific implementation schemes, the high heat transfer aluminum alloy material is heated to 300-500°C, for example, 300°C, 400°C, 500°C, etc., and extruded by an extruder to obtain a high heat transfer aluminum alloy embryo tube; preferably, the extrusion outlet temperature is controlled at 520-570°C. The high heat transfer aluminum alloy embryo tube obtained by extrusion is cooled in water and then dried, such as by compressed air drying, so as to facilitate the storage of the high heat transfer aluminum alloy embryo tube and prevent the base from being corroded.
[0032] A fourth aspect of the present invention relates to a production process of a high heat transfer and high corrosion resistance aluminum tube, comprising the following steps:
[0033] Hot dip galvanizing step: preheat the state A aluminum tube online, preferably, the preheating temperature is 480-500°C; then enter the zinc pot for hot dip galvanizing treatment; the state A aluminum tube is a high heat transfer aluminum alloy embryo tube or an internal spiral tooth aluminum tube; preferably, the zinc liquid contains 10-20wt% aluminum element, 0.1-0.6wt% silicon element, and the rest is zinc and inevitable impurities; the temperature of the zinc liquid is 480-550°C, which is conducive to the adhesion of the zinc liquid on the substrate, so that the zinc-aluminum composite coating finally obtained has a better surface state; the state A aluminum tube stays in the zinc liquid for 2-5 seconds, and after removing the excess zinc liquid, the state B aluminum tube is obtained; the residence time should not exceed this range, too long residence time affects production efficiency and there is a risk of tube breakage, and too short residence time affects the coating quality;
[0034] Online annealing step: anneal the aluminum tube in state B online at a holding temperature of 450-480°C, then cool it in water, dry it after cooling, and obtain the aluminum tube in state C; the holding temperature of annealing should not exceed the above range. If it is too high, it may cause excessive local zinc content and thus cause melt-through problems;
[0035] Aging step: Aging treatment is performed on the C state aluminum tube at a temperature and time of (150-180)°C × (3-7) h to obtain an aluminum tube with high heat transfer and high corrosion resistance.
[0036] For some specific implementation schemes, the aluminum content in the zinc liquid can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, etc., and the silicon content can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, etc.; the residence time of the A state aluminum tube in the zinc liquid can be 2 seconds, 3 seconds, 4 seconds, 5 seconds, etc.
[0037] For some specific implementation schemes, in the hot-dip galvanizing step, an annular air knife is used to blow the aluminum tube surface to remove excess zinc liquid, and the thickness and thickness stability of the surface zinc-aluminum composite coating can be regulated by adjusting the angle and air pressure of the annular air knife. The thickness of the zinc-aluminum composite coating is 50 to 800 μm, and the thickness error is within ±10%, thereby ensuring that a stable, thickness-controllable, 100% coverage zinc-aluminum alloy coating is formed on the outer surface of the aluminum tube.
[0038] In some specific implementation schemes, the inner spiral tooth aluminum tube is obtained by subjecting a common round aluminum tube in a high heat transfer aluminum alloy embryo tube to primary drawing, spiral tooth forming, and secondary drawing in sequence; wherein,
[0039] The first drawing step is to cold draw the ordinary round aluminum tube in the high heat transfer aluminum alloy embryo tube to a preset size to obtain an X-state aluminum tube;
[0040] The spiral tooth forming step is to perform a thread tooth forming process on the inner surface of the X-state aluminum tube to obtain a Y-state aluminum tube;
[0041] The secondary drawing step is to reduce the diameter of the Y-state aluminum tube by air drawing to eliminate the surface thread marks, and then straighten it to obtain the internal spiral tooth aluminum tube.
[0042] A fifth aspect of the present invention relates to a high heat transfer and high corrosion resistance aluminum tube, which is manufactured by the above production process and is a common round aluminum tube, a straight tooth aluminum tube or an inner spiral tooth aluminum tube with only the outer surface galvanized; the thickness of the zinc-aluminum composite coating is 50-800 μm, and the thickness error is within ±10%; before galvanizing:
[0043] For ordinary round aluminum tubes, the outer diameter is 5 to 35 mm and the wall thickness is 0.4 to 3 mm;
[0044] For straight tooth aluminum tube, the outer diameter is 5-35mm, the wall thickness is 0.4-3mm, the tooth height is 0.10-0.30mm, and the number of teeth is 20-65;
[0045] For the internal spiral tooth aluminum tube, the tooth wall thickness is 0.4-0.8mm, the thread angle is 15-35°, the tooth height is 0.15-0.30mm, and the number of teeth is 20-60.
[0046] Compared with the prior art, the present invention has the following technical effects:
[0047] 1) Adjusting the element ratio improves thermal conductivity; the annealed room temperature thermal conductivity of ordinary 3003 alloy is about 180-195W / (m·K), and the thermal conductivity of the present invention is improved by more than 10% compared with the annealed room temperature thermal conductivity; and the adjustment of the element ratio also balances the cold working performance and corrosion resistance of the matrix, and has excellent tube expansion performance and corrosion resistance;
[0048] 2) High-quality zinc-aluminum composite coatings can be obtained by precisely controlling the composition, temperature and residence time of the zinc pot and removing excess zinc liquid. Compared with the linear concentration zinc-aluminum composite coating obtained by the method of surface zinc spraying and then infiltration, the present invention obtains a zinc-aluminum composite coating with stable and uniform composition on the surface of the aluminum tube, so it can effectively resist external corrosion and reduce perforation leakage. The SWAAT life of 0.5mm thick aluminum tube is stably more than 300 days. The present invention does not use galvanizing on the inner wall of the aluminum tube, because the inner wall of the aluminum tube is usually in a closed refrigerant service environment, and the corrosion resistance of ordinary aluminum substrates to commonly used refrigerants is very high.
[0049] 3) A short period of online annealing treatment after hot-dip galvanizing improves the bonding strength between the zinc-aluminum composite coating and the aluminum substrate, overcomes the problem of the coating being easily damaged and peeled off during cold processing processes such as tube expansion and tube bending, and the problem of coating peeling during service, and avoids local pitting corrosion of the aluminum substrate due to the loss of a continuous barrier, as well as a significant decrease in the corrosion resistance life caused by this. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with specific embodiments. Experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.
[0051] Examples 1 to 5 and comparative examples 2 to 5 are set up, and raw materials aluminum ingots, aluminum-manganese alloys, silicon blocks, aluminum-iron alloys, pure magnesium ingots, aluminum-chromium alloys, pure copper particles, pure zinc ingots, aluminum-titanium alloys and strontium are weighed according to the following alloy composition ratios to produce internally threaded aluminum tubes; the alloy composition ratios are Mn: 0.45wt%, Si: 0.08wt%, Fe: 0.07wt%, Mg: 0.12wt%, Cr: 0.06wt%, Cu: 0.10wt%, Zn: 0.12wt%, Ti: 0.15wt%, Sr: 0.009wt%, and the remainder is Al and unavoidable impurities. On this basis, comparative example 1 is set up, in which the Mn element content in comparative example 1 is 1.05wt%, the Sr element is not added, and the other alloy elements remain unchanged (the content of the main element aluminum is increased accordingly);
[0052] Smelting step: smelting the above raw materials to obtain a melt;
[0053] Refining step: using inert gas to remove inclusions and hydrogen in the melt until the hydrogen content in the melt is less than 0.15ml / 100g;
[0054] Casting steps: using a gas sliding mold semi-continuous casting method, casting at a speed of 50 mm / min when the melt temperature is in the range of 700-750°C to obtain a cast rod; adding a grain refiner AlTi5B1 into the flow trough before casting, the grain refiner addition temperature is 710-725°C, and the addition amount is 1.0% of the melt weight;
[0055] Homogenizing step: placing the cast rod in a homogenizing furnace and heating it up with the furnace, heating it up to 600°C at a heating rate of 400°C / h, keeping it warm for 10 hours, and then taking it out of the furnace for natural cooling;
[0056] Extrusion step: After the cast rod is cut to a fixed length, it is heated to 400℃ and extruded by an extruder. The extrusion outlet temperature is controlled between 520℃ and 570℃ to obtain a high heat transfer aluminum alloy embryo tube (ordinary round aluminum tube) with an outer diameter of 16mm and a wall thickness of 1.0mm. After the embryo tube is cooled in water, the surface is dried with compressed air and coiled into a warehouse for use.
[0057] Primary drawing step: continuously cold drawing the high heat transfer aluminum alloy embryo tube to a preset size to obtain an X-state aluminum tube;
[0058] Spiral tooth forming steps: feed the X-state aluminum tube into the tooth forming machine device, and use the traditional internal thread copper tube spinning tooth forming method to form the X-state aluminum tube to obtain the Y-state aluminum tube; the tooth wall thickness is 0.5mm, the thread angle is 23°, the tooth height is 0.28mm, and the number of teeth is 50; the Y-state aluminum tube can be coiled and stored for standby;
[0059] Secondary drawing steps: the Y-state aluminum tube is subjected to air drawing and diameter reduction to eliminate the surface thread marks, and then straightened to obtain an internal spiral tooth aluminum tube; the internal spiral tooth aluminum tube has an outer diameter of 7mm and a wall thickness of 0.5mm;
[0060] Hot dip galvanizing steps: the inner spiral tooth aluminum tube is used as the A state aluminum tube, and the A state aluminum tube is preheated online to 480-500°C; then it is sent into the hot dip galvanizing zinc pot, stays for a certain period of time, and the outer surface of the A state aluminum tube is hot dip galvanized; after the excess zinc liquid is blown away by an annular air knife, it is cooled in a water tank and coiled to obtain a B state aluminum tube; the angle and air pressure of the annular air knife are adjusted to control the thickness of the zinc-aluminum composite coating to be 300μm;
[0061] Online annealing step: the aluminum tube in state B is annealed online at a holding temperature of 470°C for 5 seconds, and then cooled in water. After cooling, the surface is dried and coiled to obtain an aluminum tube in state C. This step is omitted in comparative example 4;
[0062] Aging step: Aging treatment is performed on the aluminum tube in state C at a temperature and time of 160°C × 4h to obtain an internally threaded aluminum tube with high heat transfer and high corrosion resistance. Comparative Example 4 directly performs aging treatment on the aluminum tube in state B at a temperature and time of 160°C × 4h.
[0063] The aluminum tubes prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to performance tests (thermal conductivity, corrosion resistance and mechanical properties), and the results shown in Table 1 were obtained.
[0064] Table 1 Process and performance test table Group Zinc pot composition (wt%) Zinc pot temperature (℃) Dwell time(s) Online annealing Thermal conductivity W / (m・K) SWAAT test life (days) Rp0.2 / MPa Rm / MPa A / % Example 1 Al: 15, Si: 0.3, the rest is zinc 500 3 yes 208 >300 50 111 38 Comparative Example 1 Al: 15, Si: 0.3, the rest is zinc 505 3 yes 186 265 51 112 37 Example 2 Al: 15, Si: 0.3, the rest is zinc 512 3 yes 212 >300 51 110 37 Comparative Example 2 Al: 8, Si: 0.3, the rest is zinc 505 3 yes 209 197 49 110 39 Example 3 Al: 15, Si: 0.3, the rest is zinc 510 3 yes 210 >300 49 110 39 Comparative Example 3 Al: 15, Si: 0.3, the rest is zinc 560 6 yes 226 Broken pipe 50 110 38 Example 4 Al: 15, Si: 0.3, the rest is zinc 506 3 yes 210 >300 50 111 39 Comparative Example 4 Al: 15, Si: 0.3, the rest is zinc 506 3 no 209 215 49 111 39 Example 5 Al: 15, Si: 0.3, the rest is zinc 506 3 yes 210 >300 50 111 39 Comparative Example 5 Al: 15, Si: 0.3, the rest is zinc 470 3 yes 198 185 49 108 39
[0065] Through the comparative experiments of the above embodiments and comparative examples, it can be found that:
[0066] ① Mn content: When the Mn content of 3 series aluminum alloy is high, the specific gravity of Mn is reduced to a certain level, and the thermal conductivity and electrical conductivity are improved by sacrificing the corrosion resistance of the substrate (compensated by zinc-aluminum composite coating), and the appropriate mechanical strength (Rp0.2, Rm, A) is maintained, thereby improving the overall performance of the product;
[0067] ②Al in the zinc pot: The Al content in the zinc liquid affects the metallurgical bonding between the zinc-aluminum composite coating and the aluminum substrate, and has a significant impact on the corrosion resistance life of the product;
[0068] ③ The residence time and temperature of the aluminum tube in the zinc pot: The residence time and temperature should be strictly controlled to avoid the problem of tube breakage during drawing, ensure the uniform thickness of the zinc-aluminum composite coating, and improve product quality; when the zinc pot temperature is low, it will affect the adhesion of the zinc-aluminum composite coating, and the zinc-aluminum composite coating will easily peel off, thereby reducing the corrosion resistance; when the zinc pot temperature is too high, it will cause problems such as tube breakage;
[0069] ④ Online annealing after hot-dip galvanizing: This step plays an important role in enhancing the bonding strength between the zinc-aluminum composite coating and the aluminum substrate and preventing coating peeling and blistering. It is a key process to ensure the long-term stability of the product.
[0070] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high heat transfer aluminum alloy material, characterized in that: Elements including the following components: Mn: 0.35~0.55wt%, Si: 0.05~0.13wt%, Fe: 0.05~0.13wt%, Mg: 0.06~0.15wt%, Cr: 0.03~0.10wt%, Cu: 0.05~0.15wt%, Zn: 0.07~0.15wt%, Ti: 0.05~0.20wt%, Sr: 0.008~0.012wt%, and the balance is Al and unavoidable impurities.
2. The high heat transfer aluminum alloy material according to claim 1, characterized in that: Elements including the following components: Mn: 0.45wt%, Si: 0.08wt%, Fe: 0.07wt%, Mg: 0.12wt%, Cr: 0.06wt%, Cu: 0.10wt%, Zn: 0.12wt%, Ti: 0.15wt%, Sr: 0.009wt%, and the balance is Al and inevitable impurities.
3. A production process of high heat transfer aluminum alloy material, characterized in that: The following steps are involved: Melting step: weighing raw materials according to the weight percentage of the elements in the high heat transfer aluminum alloy material of claim 1 and melting them to obtain a melt; preferably, the raw materials include aluminum ingots, aluminum-manganese alloys, silicon blocks, aluminum-iron alloys, pure magnesium ingots, aluminum-chromium alloys, pure copper particles, pure zinc ingots, aluminum-titanium alloys and strontium; Refining step: removing inclusions and hydrogen in the melt by inert gas refining or refining agent refining; preferably, the hydrogen content in the melt is ensured to be less than 0.15 ml / 100 g after refining; Casting step: when the melt temperature is in the range of 700-750° C., casting at a speed of 40-80 mm / min to obtain a cast rod; preferably, adding a grain refiner into the flow channel before casting; Homogenization step: heating the cast rod to between 550 and 610°C at a heating rate of not less than 400°C / h for 5 to 12 hours, and then cooling naturally.
4. The production process according to claim 3, characterized in that: The grain refiner is AlTi5B1 and / or AlTi5B0.2, the grain refiner adding temperature is 710-725°C, and the adding amount is 0.5%-1.0% of the melt weight.
5. A high heat transfer aluminum alloy embryo tube, characterized in that: The embryo tube is a straight-tooth aluminum tube or a common round aluminum tube, which is made by first heating and then extruding the high heat transfer aluminum alloy material of claim 1; preferably, the outer diameter of the embryo tube is 4-40 mm and the wall thickness is 0.4-5 mm.
6. The high heat transfer aluminum alloy embryo tube according to claim 5, characterized in that: The high heat transfer aluminum alloy material is heated to 300-500°C and extruded through an extruder to obtain a high heat transfer aluminum alloy embryo tube. Preferably, the extrusion outlet temperature is controlled at 520-570°C. The high heat transfer aluminum alloy embryo tube obtained by extrusion is cooled in water and then dried.
7. A production process for high heat transfer and high corrosion resistance aluminum tube, characterized in that: The following steps are involved: Hot-dip galvanizing step: the A-state aluminum tube is subjected to online preheating treatment and then hot-dip galvanizing treatment, the A-state aluminum tube is the ordinary round aluminum tube or the internal spiral tooth aluminum tube as described in claim 5 or 6; preferably, it is preheated to 480-500°C; the temperature of the zinc liquid is 480-550°C; the residence time of the A-state aluminum tube in the zinc liquid is 2-5 seconds, and after removing the excess zinc liquid, the B-state aluminum tube is obtained; preferably, the zinc liquid contains 10-20wt% of aluminum element, 0.1-0.6wt% of silicon element, and the rest is zinc and unavoidable impurities; Online annealing step: the aluminum tube in state B is annealed online at a holding temperature of 450-480°C, then cooled in water, and dried to obtain the aluminum tube in state C; Aging step: Aging treatment is performed on the C state aluminum tube at a temperature and time of (150-180)°C × (3-7) h to obtain an aluminum tube with high heat transfer and high corrosion resistance.
8. The production process according to claim 7, characterized in that: In the hot-dip galvanizing step, an annular air knife is used to blow the surface of the aluminum tube to remove excess zinc liquid.
9. The production process according to claim 7, characterized in that: The inner spiral tooth aluminum tube is obtained by successively subjecting the ordinary round aluminum tube according to claim 5 or 6 to primary drawing, spiral tooth forming, and secondary drawing; wherein, The first drawing step is to cold draw the ordinary round aluminum tube to a preset size to obtain an X-state aluminum tube; The spiral tooth forming step is to perform a thread tooth forming process on the inner surface of the X-state aluminum tube to obtain a Y-state aluminum tube; The secondary drawing step is to reduce the diameter of the Y-state aluminum tube by air drawing to eliminate the surface thread marks, and then straighten it to obtain the internal spiral tooth aluminum tube.
10. A high heat transfer and high corrosion resistance aluminum tube, characterized in that: Made by the production process described in any one of claims 7 to 9, it is an ordinary round aluminum tube, a straight-tooth aluminum tube or an internal spiral-tooth aluminum tube with only the outer surface galvanized; the thickness of the zinc-aluminum composite coating is 50 to 800 μm, and the thickness error is within ±10%; before galvanizing: For ordinary round aluminum tubes, the outer diameter is 5 to 35 mm and the wall thickness is 0.4 to 3 mm; For straight tooth aluminum tube, the outer diameter is 5-35mm, the wall thickness is 0.4-3mm, the tooth height is 0.10-0.30mm, and the number of teeth is 20-65; For the internal spiral tooth aluminum tube, the tooth wall thickness is 0.4-0.8mm, the thread angle is 15-35°, the tooth height is 0.15-0.30mm, and the number of teeth is 20-60.